Skp2 is a Promising Therapeutic Target in Breast Cancer - Wang, Zhiwei; Fukushima, Hidefumi; Inuzuka, Hiroyuki; Wan, Lixin; Liu, Pengda; Gao, Daming; Sarkar, Fazlul H.; Wei, Wenyi (Frontiers in Oncology, 2012)
Breast cancer is the most common type of cancer among American women, and remains the second leading cause of cancer-related death for female in the United States. It has been known that several signaling pathways and various factors play critical roles in the development and progression of breast cancer, such as estrogen receptor, Notch, PTEN, Her2, PI3K/Akt, BRCA1 and BRCA2. Emerging evidence has shown that the F-box protein Skp2 (S-phase kinase associated protein 2) also plays an important role in the pathogenesis of breast cancer. Therefore, in this brief review, we summarize the novel functions of Skp2 in the pathogenesis of breast cancer. Moreover, we provide further evidence regarding the state of our knowledge toward the development of novel Skp2 inhibitors especially natural “chemopreventive agents” as targeted approach for the prevention and/or treatment of breast cancer.